2021
DOI: 10.1097/sla.0000000000004893
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Cytoreductive Treatment With BRAF/MEK Inhibition of Prior Unresectable Regionally Advanced Melanoma to Allow Complete Surgical Resection, REDUCTOR

Abstract: Objective:To evaluate the potency of short-term neoadjuvant cytoreductive therapy with dabrafenib plus trametinib (BRAF and MEK inhibitor) to allow for radical surgical resection in patients with unresectable locally advanced melanoma.Summary Background Data:Approximately 5% of stage III melanoma patients presents with unresectable locally advanced disease, making standard of care with resection followed by adjuvant systemic therapy impossible. Although neoadjuvant targeted therapy has shown promising results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…In addition to these two studies, the recently published results of the REDUCTOR trial demonstrated that short-term neoadjuvant cytoreductive therapy with dabrafenib plus trametinib allowed radical resection of metastases in 81% of patients with prior unresectable locally advanced melanoma. 30 Optimization of neoadjuvant immunotherapy in melanoma: suggestions for future progress Altogether the above-mentioned studies show that neoadjuvant systemic therapy may play a significant role in locoregionally advanced melanoma that carries a high risk of relapse and death with surgery alone (table 1). Indeed, the results reported in these trials demonstrate that Open access neoadjuvant immunotherapy and TT are active and associated with high pCR rates and improved RFS.…”
Section: Nivolumab Plus Relatlimabmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these two studies, the recently published results of the REDUCTOR trial demonstrated that short-term neoadjuvant cytoreductive therapy with dabrafenib plus trametinib allowed radical resection of metastases in 81% of patients with prior unresectable locally advanced melanoma. 30 Optimization of neoadjuvant immunotherapy in melanoma: suggestions for future progress Altogether the above-mentioned studies show that neoadjuvant systemic therapy may play a significant role in locoregionally advanced melanoma that carries a high risk of relapse and death with surgery alone (table 1). Indeed, the results reported in these trials demonstrate that Open access neoadjuvant immunotherapy and TT are active and associated with high pCR rates and improved RFS.…”
Section: Nivolumab Plus Relatlimabmentioning
confidence: 99%
“…In addition to these two studies, the recently published results of the REDUCTOR trial demonstrated that short-term neoadjuvant cytoreductive therapy with dabrafenib plus trametinib allowed radical resection of metastases in 81% of patients with prior unresectable locally advanced melanoma. 30 …”
Section: Melanomamentioning
confidence: 99%
“…In the surgery group pCR was achieved in 35% (7/16), pPR in 35%, and no response in three, i.e., 15%. The 2-year OS was 84% [ 10 ]. As a consequence of the above-mentioned trials, in a recent pooled analysis from the International Neoadjuvant Melanoma Consortium covering 192 patients, only 51 received neoadjuvant targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…About five to 15% of stage III melanoma patients are unable to undergo up-front resection due to the extent of their tumors, location of the tumor, and/or the anticipated morbidity of the surgery. In such cases, standard care with surgical resection followed by adjuvant treatment is impossible [ 10 , 11 ]. Moreover, up to 10% of melanoma patients develop locoregional recurrence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation